The New Leadership: Managing Participation in Organizations - Miluwi, Joshua 0. (Gyan Management Journal, 2013)
There has been a growth in emphasis on culture as a factor impacting on the performance of managers within multinational corporations. Models of cross cultural and intercultural effectiveness have been suggested that moderate the traditional models of performance management. However, in the area of leadership there has been a continued focus applying a two factor model to leader behaviour ignoring, for the most part, cultural issues. In this paper we initially review the development of this western model of leader behaviour. Subsequently we discuss its limitations in western and Asian contexts. Finally, through consideration of a 'representation/participation' dimension that is evident in empirical studies in both western and Asian literature, but which has been largely ignored when the construct of a leader behaviour is operationa/ised, we derive a new, three-dimensional model of leadership and discuss its applicability to the studyofcross-cultural leader behaviour.
Keywords: Leadership; Consideration; Initiating Structure; Participation; Cross-cultural